EXPERIENCE OF PROVIDING EFFECTIVE MECHANISMS FOR SMALL BUSINESS INNOVATIVE DEVELOPMENT - Irina A. Dudakova; Yulia V. Gladkova (Advanced Engineering Research)
Small business situation, characteristics and trends of its development in the economically developed countries are analyzed. On the basis of the western experience in creating support structures and promoting the innovative development of small business, the primary areas of its adaptation to the Russian realities are formulated.